2002
DOI: 10.1021/bi025603x
|View full text |Cite
|
Sign up to set email alerts
|

Prime Site Binding Inhibitors of a Serine Protease:  NS3/4A of Hepatitis C Virus

Abstract: Serine proteases are the most studied class of proteolytic enzymes and a primary target for drug discovery. Despite the large number of inhibitors developed so far, very few make contact with the prime site of the enzyme, which constitutes an almost untapped opportunity for drug design. In the course of our studies on the serine protease NS3/4A of hepatitis C virus (HCV), we found that this enzyme is an excellent example of both the opportunities and the challenges of such design. We had previously reported on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…The result of these conformational changes is a reorientation of the residues of the catalytic triad which is more favorable for proton shuttling during catalysis. A number of studies provided evidence that structural rearrangements leading to a fully activated protease are induced not only by binding of the cofactor but also by the substrate, as shown for the competitive inhibition of the NS3 protease by its cleavage products (2,3,24,25,38). Based on these findings, the hepatitis C virus enzyme has been described as an induced-fit protease (6,39).…”
mentioning
confidence: 99%
“…The result of these conformational changes is a reorientation of the residues of the catalytic triad which is more favorable for proton shuttling during catalysis. A number of studies provided evidence that structural rearrangements leading to a fully activated protease are induced not only by binding of the cofactor but also by the substrate, as shown for the competitive inhibition of the NS3 protease by its cleavage products (2,3,24,25,38). Based on these findings, the hepatitis C virus enzyme has been described as an induced-fit protease (6,39).…”
mentioning
confidence: 99%
“…Prior to our work on NS3/4A, 44,46 other authors had already shown that prime site binding could be an effective component of a serine protease inhibitor, 48,49 but the previously described inhibitors all established crucial contacts in the nonprime region of the enzyme. The NS3 inhibitors described above represent therefore the first example of purely prime-site inhibitors of a serine protease.…”
Section: "Collected Product" Inhibitors For a Serine Proteasementioning
confidence: 91%
“…These included kinetic analysis of competitive behavior, site-directed mutagenesis, comparison with the SAR of the P-PЈ inhibitors, a probe displacement assay, CD, and NMR, albeit in the absence of the NS4A cofactor. 46 CD in particular showed that binding of compound 1 to NS3/4A causes a change in the near-uv spectrum of the protease, with a small but consistent increase of intensity between 252 and 292 nm, indicating that, like for the P-PЈ decapeptides, an induced-fit mechanism is associated with the inhibition process. Selective N-methylation was then used to assess the backbone hydrogen-bonding pattern.…”
Section: Prime-site Inhibitorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Most of the inhibitors so far developed have as the starting point the hexapeptide product inhibitors of the enzyme [9][10][11]. Among them, a macrocyclic peptidomimetic shows a marked antiviral effect in clinical trials after oral administration [12].…”
Section: Introductionmentioning
confidence: 99%